2009
DOI: 10.1172/jci37007
|View full text |Cite
|
Sign up to set email alerts
|

GRP78 expression inhibits insulin and ER stress–induced SREBP-1c activation and reduces hepatic steatosis in mice

Abstract: Hepatic steatosis is present in insulin-resistant obese rodents and is concomitant with active lipogenesis. Hepatic lipogenesis depends on the insulin-induced activation of the transcription factor SREBP-1c. Despite prevailing insulin resistance, SREBP-1c is activated in the livers of genetically and diet-induced obese rodents. Recent studies have reported the presence of an ER stress response in the livers of obese ob/ob mice. To assess whether ER stress promotes SREBP-1c activation and thus contributes to li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

34
520
6
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 636 publications
(573 citation statements)
references
References 59 publications
34
520
6
7
Order By: Relevance
“…24 Gene knockdown of GRP78 has been demonstrated to block ER stress-induced autophagosome formation in human cells. 24,51 These results are in line with our finding that treatment with siGRP78 attenuated the augmented expression of LC3-II in RVLM of SHR. Together with our finding of an involvement of ER stress-associated autophagy in hypertension phenotype of SHR, it is conceivable that under the scenario of chronic ER stress, as in RVLM of SHR, ER stress-associated autophagy might play a predominant role in the pathogenesis of hypertension.…”
Section: Discussionsupporting
confidence: 87%
“…24 Gene knockdown of GRP78 has been demonstrated to block ER stress-induced autophagosome formation in human cells. 24,51 These results are in line with our finding that treatment with siGRP78 attenuated the augmented expression of LC3-II in RVLM of SHR. Together with our finding of an involvement of ER stress-associated autophagy in hypertension phenotype of SHR, it is conceivable that under the scenario of chronic ER stress, as in RVLM of SHR, ER stress-associated autophagy might play a predominant role in the pathogenesis of hypertension.…”
Section: Discussionsupporting
confidence: 87%
“…Despite a modest association between TRIB3 transcripts and transcripts encoding SREBP-1c, recent studies have shown that nuclear import of SREBP-1c is enhanced by endoplasmic reticulum stress, which is implicated in insulin resistance [12]. We therefore directly determined effects of SREBP-1c and PPARGC1B on transcriptional regulation of the human TRIB3 gene, in co-transfection experiments using HepG2 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Upregulation of Srebp‐1c expression was found in the liver of obese mice (Ferré & Foufelle, 2010; Kammoun et al ., 2009). Liver‐specific Srebp‐1c transgenic mice showed hepatic steatosis (Knebel et al ., 2012), suggesting that Srebp‐1c was responsible for the pathogenesis of this condition.…”
Section: Discussionmentioning
confidence: 99%